Analisis Kompensasi dan Lingkungan Kerja terhadap Kepuasan Kerja serta Implikasinya terhadap Kinerja Pegawai Perangkat Desa di Kecamatan Cireunghas Kabupaten Sukabumi - Burhanudin Ruslan; Rochani Mulyani, Sri; Yuliaty, Farida; Djogo, Y Ony; Paramartha, Vip; Kosasih, Kosasih (Jurnal Ragam Pengabdian, 2026)
The limited literature on the work behavior of village government officials in environments with constrained facilities and incentive systems motivates this study. It examines the effects of compensation and work environment on job satisfaction and their implications for the performance of village officials in Cireunghas District, Sukabumi. Using a quantitative descriptive and verification approach, the study involved all 55 village officials from five villages through a total sampling technique. Data were collected using a Likert-scale questionnaire and analyzed with path analysis. The findings indicate that compensation has no significant direct effect on job satisfaction (p = 0.066) or performance (p = 0.669). In contrast, the work environment has a positive and significant effect on both job satisfaction and performance (p < 0.001), while job satisfaction significantly improves performance (p < 0.001). Job satisfaction fully mediates the relationship between compensation and performance and partially mediates the relationship between the work environment and performance. The study recommends prioritizing improvements in the work environment, timely incentives, and modernization of digital work facilities to enhance village public service performance.